A cross sectional study on community prevalence and treatment practice of hypertension with household awareness about it in semi urban Mangalore - A pilot study - N., Navya; Kundapur, Rashmi; Kiran, N. Udaya (Journal of Health and Allied Sciences NU, 2015)
Introduction: Hypertension, also known as high or raised blood pressure, is a global public health issue and is the major contributory factor for the burden of heart disease, stroke, renal failure, premature mortality and morbidity worldwide.Objective : 1. To determine the community prevalence of hypertension.2. To Assess the Household Awareness Of hypertension.3. To study the pattern and regularity of treatment in hypertensives.Methodology: A cross sectional study was carried out in 40 Households of Grama-Kshema Project in Kuthar and Manjanady villages (semi urban ) which belong to the field practice area of K.S. Hegde Medical Academy, Mangalore. A structured Questionnaire was used to collect data. Questions on awareness were scored and analyzed.Result: The community prevalence of hypertension among the households surveyed was 9.6 percent out of which 12.5 % were female and 5.9 % were male. Among them 46.7% were in the age group 51-70 years, 40% in the age group 31-50 years and 13.3% in the age group above 70 years.40 % of hypertensive visit their doctor on monthly basis.66.7% of the hypertensives visit private dispensary for their treatment and follow up. 93.3% are on anti-hypertensives of which 33.3 % use calcium channel blockers. Awareness scoring showed that 40% had poor score and 37.5 % average score.Conclusion: In the present study the prevalence of hypertension was found to be low. Among those diagnosed of hypertension, majority of them were females. Most of the hypertensive's visit private dispensaries on monthly basis. Awareness of Hypertension among the households was poor.
Keywords: Hypertension; Awareness; Prevalence